IgE type multiple myeloma exhibits hypermutated phenotype and tumor reactive T cells. Issue 10 (17th October 2022) - Kehl, Niklas; Kilian, Michael; Michel, Julius; Wagner, Tim R; Uhrig, Sebastian; Brobeil, Alexander; Sester, Lilli-Sophie; Blobner, Sven; Steiger, Simon; Hundemer, Michael; Weinhold, Niels; Rippe, Karsten; et al.
Abstract : Multiple myeloma (MM) is a hematological malignancy originating from malignant and clonally expanding plasma cells. MM can be molecularly stratified, and its clonal evolution deciphered based on the Ig heavy and light chains of the respective malignant plasma cell clone. Of all MM subtypes, IgE type MM accounts for only <0.1% of cases and is associated with an aggressive clinical course and consequentially dismal prognosis. In such malignancies, adoptive transfer of autologous lymphocytes specifically targeting presented (neo)epitopes encoded by either somatically mutated or specifically overexpressed genes has resulted in substantial objective clinical regressions even in relapsed/refractory disease. However, there are no data on the genetic and immunological characteristics of this rare and aggressive entity. Here, we comprehensively profiled IgE type kappa MM on a genomic and immune repertoire level by integrating DNA- and single-cell RNA sequencing and comparative profiling against non-IgE type MM samples. We demonstrate distinct pathophysiological mechanisms as well as novel opportunities for targeting IgE type MM. Our data further provides the rationale for patient-individualized neoepitope-targeting cell therapy in high tumor mutation burden MM.